(3GdeSDhdjI GdeUQajI aj GdGYJeGO GdeGdjs - (3dHfi YeQ(B, (3eSbGhjs; (3gGfj OhjOGQ(B, s ((3HjQhJ(B:s (3efThQGJ GdMdHj GdMbhbjI(B,s, 2006)
(3YbO aJM GdGYJeGO Hjf GdWHjYI GdbGfhfjI GdNGUI hGdNVhY ddCMcGe GdYGeI ddehLHGJ hGdYbhO, GdeSDhdjI GdeUQajI Yf GdJYSa aj GSJYeGd Mbg aS eYQV YedjGJ GdJehjd, eSDhdjI GdHfc Yf YOe JfajPg dehLHGJg GdYbOjI aj GWGQ YedjGJ GdJehjd GdeUQaj, CSGS GdeSDhdjI GdeUQajI Yf YedjGJ GdGYJeGO GdeGdj(B: (3eHfi GdeSDhdjI GdeUQajI Yf YedjGJ GdGYJeGO GdeGdj, aj ebJVjGJ KHhJ GdeSDhdjI GdeUQajI Yf YedjGJ GdGYJeGO GdeGdjs
(3HHdjhZQGajG(B: (3U(B325-336s
Keywords: (3GdCMcGes; (3GdHfhc(B-(3GYJeGOGJs; (3GdYbhOs